FAKTOR-FAKTOR YANG MEMPENGARUHI RISIKO SISTEMATIS PERUSAHAAN INDEX LQ-45 - Intan Adi Irana; Damayanti Damayanti (J-MACC, 2023)
This study aims to prove the effect of leverage, liquidity, and asset growth on systematic risk in companies that are members of the LQ-45 index on the Indonesia Stock Exchange. The population used in this study is companies that are members of the LQ-45 index on the Indonesia Stock Exchange in 2017-2021. The sample selection technique uses purposive sampling. Data analysis technique using multiple linear regression analysis. The results of this study indicate that leverage has a significant positive effect on systematic risk, liquidity has an insignificant positive effect and asset growth has an insignificant negative effect on systematic risk of companies listed on the LQ-45 index on the Indonesia Stock Exchange. The value of Adjusted R² is 0.210, which means that 21% of the variation in the systematic risk of companies listed on the LQ-45 index on the Indonesia Stock Exchange can be explained by the three independent variables, namely leverage, liquidity and asset growth. While the remaining 79% is explained by other variables not examined in this study.